Critical success factors of a bottom up urban design process to deliver sustainable urban designs - Dias, Nuwan; Keraminiyage, Kaushal; Amaratunga, Dilanthi; Curwell, Steve (International Journal of Strategic Property Management, 2018)
A sustainable urban environment caters for peoples’ need. When the needs of the people are addressed, it increases the property values and attracts investors. The current urban design process is top-down, i.e., Designers and planners play the key role and the community has less engagement. There are serious criticisms of this process as it may not touch the “ground” level requirements, and therefore, these projects will fail to create sustainable environments. Accordingly, to overcome the drawbacks of the current top-down process, researches have discussed implementing a bottom-up process in order to deliver sustainable urban designs. Based on this argument this paper discusses what are the positive and negative implications of a bottom up urban design process and what are the critical success factors which can be derived from a bottom-up urban design process in order to deliver sustainable urban environments.